Analysis of stable states in global savannas – a response to Staver and Hansen. Issue 8 (10th May 2015) - Hanan, Niall P.; Tredennick, Andrew T.; Prihodko, Lara; Bucini, Gabriela; Dohn, Justin
Abstract Staver & Hansen (2015, Global Ecology and Biogeography, doi: 10.1111/geb.12285) comment on our recent paper (Hanan et al., Global Ecology and Biogeography, 2014, 23, 259–263) in which we argue that classification and regression tree methods used with remote sensing data to predict tree cover may bias inference of bifurcations in savanna vegetation communities. While we agree with several of their comments, we remain unconvinced that a remote sensing product based on an inherently discontinuous statistical approach can, or should, be used to test for discontinuities.